A Cross-Lagged Panel Analysis of the Relationship Between Neighborhood Sense of Community and School Sense of Community - Prati, Gabriele (Eur J Psychol, 2019)
Neighborhood sense of community and school sense of community have been associated with important outcomes for adolescents. However, the complex interplay between neighborhood sense of community and school sense of community among adolescents is not clear. Moreover, the studies showing an association between neighborhood sense of community and school sense of community have been cross-sectional. The present study investigated the directionality of the relationship between neighborhood sense of community and school sense of community using a longitudinal cross-lagged design. Using structural equation modeling, a cross-lagged panel analysis revealed that school sense of community at Time 1 significantly predicts neighborhood sense of community at Time 2 even after controlling for neighborhood sense of community at Time 1. However, neighborhood sense of community at Time 1 did not predict school sense of community at Time 2. Results of this study support the theory that school sense of community can provide students with a bridge between school and community.